A comparison of the effects of tributyltin chloride and triphenyltin chloride on cell proliferation, proapoptotic p53, Bax, and antiapoptotic Bcl-2 protein levels in human breast cancer MCF-7 cell line. Issue 4 (June 2015) - Fickova, Maria; Macho, Ladislav; Brtko, Julius
Highlights Tributyltin chloride (TBT) and triphenyltin chloride (TPT) were tested. TBT is more effective than TPT in inhibiting growth of MCF7 breast cancer cells. TBT markedly enhanced p53 protein expression by time and dose dependent manner. TBT and TPT have similar mild stimulatory effects on Bax protein expression. TPT rapidly and sharply inhibits Bcl-2 protein expression during 24 h interval.